Structural equation modeling of eating attitude based on self-differentiation, emotional reactivity and negative urgency with the mediation of emotion regulation difficulty in girls - Roshandel, Azam; Gholami Turan Poshti, Marzieh; Havasi Somar, Nahid; Shahnazari, Mahdi (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This research was conducted with the aim of modeling the structural equations of eating attitude based on self-differentiation, emotional reactivity and negative urgency with the mediation of emotion regulation difficulty in girls. Methods: The method of conducting the research was correlational and structural equation modeling. The statistical population of this research included all young girls, of which 284 were selected by cluster sampling. The research tools include the Garner and Garfinkel (1979) eating attitude test, the short form of the Drake, Murdock, Marszalek and Barber (2015) differentiation inventory, Lynham and Miller (2004) impulsive behavior scale, Watson, Clark, and Tellgen's positive and negative affect scale. (1988) and the emotion regulation difficulty scale was Gratz and Roemer (2004). To collect data, descriptive and inferential statistics and structural equations were used using SPSS26 and AMOS24 software. Bootstrap method was used in MACRO program to analyze mediating relationships. Results: The findings showed that the relationship between the structural model of eating attitude based on self-differentiation, emotional reactivity (positive and negative emotional) and negative urgency with the mediation of emotion regulation difficulty has a good fit (P